2019
DOI: 10.1080/03009742.2019.1602163
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for development and persistence of chronic widespread pain in spondyloarthritis: a population-based two-year follow-up study

Abstract: To study chronic widespread pain (CWP) over time in patients with spondyloarthritis (SpA), and to identify risk factors for development and persistence of CWP. Methods: In this cohort study with baseline and 2.5 year follow-up postal surveys, patients with ankylosing spondylitis (AS) and undifferentiated spondyloarthritis (USpA) (47% women) answered questions regarding pain, and were categorized as no chronic pain (NCP), chronic regional pain (CRP), or CWP. For each risk factor candidate (disease duration, bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 44 publications
2
14
0
1
Order By: Relevance
“…The need to develop effective prevention is underlined by the 10-11% prevalence of WSP in the general population, which is associated with high socioeconomic costs. 20,21 Some studies report a relatively low reduction of the spreading of pain over time, 23,62 but there are also studies indicating a larger transition between different extents of spreading. 47,63 The latter may indicate that widespread pain is not as static as previously assumed but instead can deteriorate or improve.…”
mentioning
confidence: 99%
“…The need to develop effective prevention is underlined by the 10-11% prevalence of WSP in the general population, which is associated with high socioeconomic costs. 20,21 Some studies report a relatively low reduction of the spreading of pain over time, 23,62 but there are also studies indicating a larger transition between different extents of spreading. 47,63 The latter may indicate that widespread pain is not as static as previously assumed but instead can deteriorate or improve.…”
mentioning
confidence: 99%
“…This study does not imply that there is likely a difference in the experience of living with CWP between men and women, however, there might be a difference in how men and women in general experience their journey to CWP. It is well known from previous studies that the prevalence of CWP is higher among women and that women are at increased risk for persistent CWP [13][14][15], which justify this decision to analyze experiences from men and women separately. This study does, however, highlight the importance of conductance of a similar study including only men.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Although more research is needed to better understand CWP over a life span, it is possible that fluctuating CWP and persistent CWP may represent different dimensions of the condition. One of the factors predicting persistence of CWP over time is female gender [14,15]. It is, thereby, possible that men and women to some extent experience their pain journey over a life span differently, which should be considered when including men and women in the same study.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term studies have shown that CWP can only be regarded as persistent for approximately 50% of the population (Landmark et al, 2019), which suggests that half of the individuals reporting CWP at a specific point in time will fluctuate between CWP, and chronic pain in several pain sites but not fulfil the criteria for CWP, or no chronic pain over time. Female gender is one of the factors that predict the persistence of CWP (Mogard et al, 2019;Mundal et al, 2014). Among women, the prevalence of chronic pain seems to increase the most in the age group between 35 and 50 years old (Bergman et al, 2001), suggesting a potentially increased vulnerability for chronic pain and CWP during middle age in women.…”
Section: Introductionmentioning
confidence: 99%